1998
DOI: 10.1090/s0025-5718-98-00913-2
|View full text |Cite
|
Sign up to set email alerts
|

Total variation diminishing Runge-Kutta schemes

Abstract: Abstract. In this paper we further explore a class of high order TVD (total variation diminishing) Runge-Kutta time discretization initialized in a paper by Shu and Osher, suitable for solving hyperbolic conservation laws with stable spatial discretizations. We illustrate with numerical examples that non-TVD but linearly stable Runge-Kutta time discretization can generate oscillations even for TVD (total variation diminishing) spatial discretization, verifying the claim that TVD Runge-Kutta methods are importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
1,210
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 2,088 publications
(1,227 citation statements)
references
References 16 publications
7
1,210
0
10
Order By: Relevance
“…We discretize the spatial operator |▽ϕ| in (7) and (8) using the fifth-order weighted essentially non-oscillatory (WENO) method [27,28], and we discretize pseudo-time in (8) using the third-order total variation-diminishing Runge-Kutta method (TVD-RK) from [23] and [24]. Due to the computational cost and the complexity of our tumor system, we currently discretize time in (7) using a forward Euler algorithm and a small step size.…”
Section: Narrow Band/local Level Set Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We discretize the spatial operator |▽ϕ| in (7) and (8) using the fifth-order weighted essentially non-oscillatory (WENO) method [27,28], and we discretize pseudo-time in (8) using the third-order total variation-diminishing Runge-Kutta method (TVD-RK) from [23] and [24]. Due to the computational cost and the complexity of our tumor system, we currently discretize time in (7) using a forward Euler algorithm and a small step size.…”
Section: Narrow Band/local Level Set Methodsmentioning
confidence: 99%
“…3. If (x i−2 , y j ) and (x i−1 , y j ) are both in Ω, then we obtain p̂i +1,j as a quadratic extrapolation of p from p i−2, j , P i−1,j , and u ℓ : (23) If (x i−1 , y j ) ∈ Ω but (x 1−2 , y j ) ∉ Ω, then we obtain p̂i +1,j by linear extrapolation from p i−1,j and p ℓ : (24) If (x i−1 , y j ) ∉ Ω, then we use the constant extrapolation p̂i +1,j = p ℓ . Note that in all cases, we require p ℓ .…”
Section: Ghost Cell Extrapolations For the Diffusionalmentioning
confidence: 99%
“…However, a possible consequence of using the higher-order schemes is the numerical instability. The Runge-Kutta methods with the total variation diminishing (TVD) property can prevent such a problem, see [34]. Considering the one-dimensional wave equation (24), the total variation of the variable ϕ can be calculated by,…”
Section: Time Integrationmentioning
confidence: 99%
“…It can be shown that the 1 st -order forward (Euler) time integration method is a basic TVD Runge-Kutta method, see [34]. The Euler method can be written as,…”
Section: • No Decreasing Values Of the Local Minimums And No Increasimentioning
confidence: 99%
See 1 more Smart Citation